Kinerja Lembaga Perkreditan Desa (LPD) Adat Demayu Desa Singakerta Kecamatan Ubud Kabupaten Gianyar - PRADNYANI, NI MADE MITA SINTYA; SUAMBA, I KETUT; ANGGRENI, I GUSTI AA LIES (Jurnal Agribisnis dan Agrowisata (Journal of Agribusiness and Agritourism); Vol.6, No.4, Oktober 2017, 2017)
Performance of Village Credit Instituion (LPD) of Demayu Singakerta Village Ubud District Gianyar Regency The Village Credit Institution (LPD) of Demayu is an institution that plays a role in the economy of the Indigenous Village of Demayu and as one of the financial institutions in rural agriculture. The development and progress of Village Credit Institutions can be seen through some of the performance namely the financial and the management performances. The purpose of the study was to determine the financial performance by using the profit-oriented ratio of financial institutions and the management performance of the Village Credit Institution (LPD) of Demayu in terms of internal and external aspects. The analytical method used to assess the financial performance was conducted by using profit-oriented ratio analysis of financial institutions while the assessment of the management performance can be seen from two aspects, i.e. the internal and the external performances. Internal performance can be analyzed from the employee satisfaction aspect and the external performance can be seen from the customer satisfaction aspect as measured by Likert scale. Based on the findings of the research, it can be concluded that the Village Credit Institution (LPD) of Demayu financial performance evaluated from current ratio, debt to asset ratio, total asset turnover were in very unfit category, while the net profit margin was fit. The management performance in terms of internal aspect obtained an overall average score of 3,97% that categorized as satisfied while the performance of management in terms of external aspects obtained an overall average score of 4.09% that is also categorized as satisfied . Suggestions that can be given: the Village Credit Institution (LPD) of Demayu should further foster their own capital so that assets increase without increasing the debt; one of them is by way of increasing credit distribution activities to the community, for performance management in terms of internal aspects, the management should more often communicate and interact with employees, for the management performance viewed from the external aspect, the management should pay more attention and improve the quality of service, and every activity carried out on the Village Credit Institution (LPD) of Demayu should be more emphasized on the concept of Tri Hita Karana.